Deteksi Kebocoran pada Pipa Natural Gas setelah Dilakukan Pengelasan dengan Menggunakan Metode Pneumatic Test di PT Unilever Oleochemical Indonesia - Bambang Kurnia; Zulfan Zulfan; Joharsah Joharsah (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
Natural gas is an essential industrial fluid, and its distribution requires a pipeline system that is safe and leak-free. Leakage in natural gas pipelines remains a major concern, as it reduces public confidence in using gas for household purposes. Therefore, testing is conducted before the pipeline network is operated. One commonly used method to detect leaks is the Pneumatic Test, which evaluates the strength and integrity of pipes and their joints according to standards for polyethylene natural gas pipelines. This test uses compressed air supplied by a compressor, with pressure and temperature measured at the inlet pipe using a pressure gauge. The study found no pressure changes or leakage throughout the test. The calculated holding time required for the pneumatic procedure was 1 hour, 26 minutes, and 8 seconds. Non-Destructive Testing (NDT) results showed that: (a) at 50% of test pressure (approximately 10 bar), the pipe held for 15 minutes with no pressure drop; (b) at 75% (around 15 bar), pressure remained stable for 15 minutes; and (c) at 100% (20 bar), pressure was maintained for 75 minutes without loss. Welding was performed using Nikko Steel electrodes (2 mm × 300 mm, 50–80 A), supported by proper safety gear and tools, and a Riland welding machine with a 400-A capacity.